NRLMSIS 2.1: An Empirical Model of Nitric Oxide Incorporated Into MSIS. Issue 10 (6th October 2022) - Emmert, J. T.; Jones, M.; Siskind, D. E.; Drob, D. P.; Picone, J. M.; Stevens, M. H.; Bailey, S. M.; Bender, S.; Bernath, P. F.; Funke, B.; Hervig, M. E.; Pérot, K.
Abstract: We have developed an empirical model of nitric oxide (NO) number density at altitudes from ∼73 km to the exobase, as a function of altitude, latitude, day of year, solar zenith angle, solar activity, and geomagnetic activity. The model is part of the NRLMSIS® 2.1 empirical model of atmospheric temperature and species densities; this upgrade to NRLMSIS 2.0 consists solely of the addition of NO. MSIS 2.1 assimilates observations from six space‐based instruments: UARS/HALOE, SNOE, Envisat/MIPAS, ACE/FTS, Odin/SMR, and AIM/SOFIE. We additionally evaluated the new model against independent extant NO data sets. In this paper, we describe the formulation and fitting of the model, examine biases between the data sets and model and among the data sets, compare with another empirical NO model (NOEM), and discuss scientific aspects of our analysis. Key Points: New nitric oxide (NO) component of NRLMSIS empirical temperature and density model, from ∼73 km to exobase Constructed within NRLMSIS 2.0 framework; NO density is coupled to MSIS temperature above ∼110 km The empirical fit is based on observations from six space‐based instruments